Spin phonon coupling and magneto-dielectric coupling in BiFeO3-TbMnO3 composite - Gupta P.K.; Ghosh S.; Kumari S.; Pal A.; Roy S.; Singh R.; Singh P.; Singh R.K.; Ghosh A.K.; Chatterjee S. (My University, 2025)
Magneto-structural and magneto-electric coupling in multiferroic composite BiFeO3-TbMnO3 have been investigated. Anomalous softening of the phonon modes was observed ∼210 K (close to the spin reorientation transition temperature T∗) in the temperature dependent Raman spectra which might be a result of spin phonon coupling in the lattice. Relaxor type ferroelectric behaviour was observed in the temperature dependent dielectric measurements where the relaxation was found near T∗. The frequency dependent dielectric study and the impedance spectroscopy revealed that the dielectric properties are a mixture of intrinsic Debye relaxation and Maxwell-Wagner relaxation arising from the space charge polarization at the interface of the composite. A large positive magneto-dielectric (MD) coupling was found near the relaxation temperature which is understood to be originated as a result of the magneto-structural coupling in the system. © 2019 IOP Publishing Ltd.